Assessment of Suicide Attempt in The Forensic Medicine Outpatient Clinic in Muğla - Kıymet, Muazzez Elçin; Ünüvar Göçeoğlu, Ümit; Yürürdurmaz, Betül; Balcı, Yasemin (The Bulletin of Legal Medicine, 2020)
Objective: Suicide attempts are causes of mortality and morbidity. Suicide attemp patients’ reports were evaluated  in Forensic Medicine outpatient clinic. It was aimed to present of sociodemographic characteristics, methods, regional characteristics, develop to recommendations for proventive measures.Materials-Methods; Between 01.06.2014-31.12.2018 were evaluated retrospectively and statisticaly.Results: 405(5.3%) of the cases attempted suicide, 263(64.9%) were women, 142(35.1%) were men, 11.8% of them (n: 48) was under 18, 84.9% (n: 344) was under 40. The majority of the cases were in the 20-29 age range, women were more present in under 19 years, and men were more present in the 30-39 age group(p
Keywords: suicide attempt; suicide method; forensic medicine; forensic report